Effect of penaeus merguiensis-translationally controlled tumor protein on TPT1 expression of heat-treated human pulp cells - Canussanun Jirachotikoon (Prince of Songkla University, 2015)
Thesis (Ph.D., (Molecular Biology and Bioinforatics))--Prince of Songkla University 2014